Mellow memories - Television Syndications, Inc.; U.S.A. Home Video ([s.l.] : U.S.A. Home Video, 1984)
Get in the mellow groove with these far-out performances by the coolest cats from the 60s and 70s.
Cherry Cherry / Neil Diamond -- Leavin' on a jet plane / John Denver -- I don't know how to love him / Helen Reddy -- Never my love / The Association -- Cry like a baby / Bobby Sherman -- Amos Moses / Jerry Reed -- Mony Mony / Tommy James and the Shondells -- I hear a symphony / Diana Ross and the Supremes -- Mr. Bojangles / Nitty Gritty Dirt Band -- Daddy don't you walk so fast / Wayne Newton -- Country roads / John Denver -- Diamonds are forever / Shirley Bassey -- Cherry Hill Park / Billy Joe Royal -- One bad apple / The Osmonds -- Gypsy woman / Brian Hyland -- Nobody but you / Loggins and Messina -- Feelin' groovy / Harpers Bizarre -- I think I love you / David Cassidy -- Alfie / Dionne Warwick -- Beautiful story / Sonny and Cher -- An American trilogy / Mickey Newbury.
VHS format.
"212-342"
Videocassette release of the 1984 program by Television Syndications, Inc.
Neil Diamond, John Denver, Helen Reddy, The Association, Bobby Sherman, Jerry Reed, Tommy James and the Shondells, Diana Ross and the Supremes, Nitty Gritty Dirt Band, Wayne Newton, John Denver, Shirley Bassey, Billy Joe Royal, The Osmonds, Brian Hyland, Loggins and Messina, Harpers Bizarre, David Cassidy, Dionne Warwick, Sonny and Cher, Mickey Newbury.
Keywords: Country music; Rock music -- United States